1990
DOI: 10.1103/physrevlett.65.705
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of x-ray emission lines from heliumlike scandium as a probe of the hyperfine interaction

Abstract: We report the first measurements of the polarization of x rays emitted from bound-bound transitions in a highly ionized He-like ion. Polarization was measured for the decay to the ground state, Is 2 'So, of the He-like Sc 19+ levels \slp l P\> \s2p 3 Pi, ls2p 3 Pi, and \s2s 3 S\. The measurements were made with the Electron Beam Ion Trap at two electron-beam energies: 4.36 and 5.62 keV. Polarization of two of the lines is strongly influenced by the hyperfine interaction with the Sc nucleus, demonstrating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(39 citation statements)
references
References 14 publications
(4 reference statements)
2
36
0
1
Order By: Relevance
“…The hyperfine levels of the ground state of atomic hydrogen give rise to the 21-cm line used in radioastronomy to image our galaxy and were the basis for the first maser (see [6]). Hyperfine line splitting is of importance in photopumped x-ray lasers [7], and hyperfine interaction affects the polarization of spectral lines used in plasma diagnostics [8]. Hyperfine interaction is sufficient to break symmetry in atoms and ions with a J=0 excited level above a J=0 ground level (typically in two-electron ions), and this can turn a very long-lived level (for example, 1s2p 3 P o 0 in heliumlike ions) into a shorter one [9], in some cases drastically so [10].…”
mentioning
confidence: 99%
“…The hyperfine levels of the ground state of atomic hydrogen give rise to the 21-cm line used in radioastronomy to image our galaxy and were the basis for the first maser (see [6]). Hyperfine line splitting is of importance in photopumped x-ray lasers [7], and hyperfine interaction affects the polarization of spectral lines used in plasma diagnostics [8]. Hyperfine interaction is sufficient to break symmetry in atoms and ions with a J=0 excited level above a J=0 ground level (typically in two-electron ions), and this can turn a very long-lived level (for example, 1s2p 3 P o 0 in heliumlike ions) into a shorter one [9], in some cases drastically so [10].…”
mentioning
confidence: 99%
“…Theoretical results: d, present results in He-like Cl ion; B, He-like Ti ions [22]. Experimental results: C, He-like Sc ion [8]; -, He-like Fe ion [9]; *, He-like Ti ion [10]; Â, Helike Si ion [11]. …”
Section: Polarization (%)mentioning
confidence: 90%
“…The measured intensity of the emitted radiation from these ions strongly depends on the angle of observation relative to the beam axis. There have been several studies reported in the literature for the polarization of radiation emitted from ions trapped in an EBIT (Henderson et al 1990;Beiersdorfer et al 1996;Taḱacs et al 1996;Gu et al 1999;Liang et al 2009a;Hu et al 2014b;Shah et al 2015). In the present study, we measured EUV spectra using CoBIT at 90…”
Section: Experiments and Data Analysismentioning
confidence: 94%
“…• with respect to the electron beam, the polarization of the emitted line radiation may therefore effect the resulting line intensities as discussed by (Liang et al 2009a;Beiersdorfer et al 1996;Henderson et al 1990). Liang et al (2009a) estimated polarization effect for the transitions in Fe VII−Fe XIV and found that for most of the observed lines, the contribution is less than 10% to the resultant intensity.…”
Section: Experiments and Data Analysismentioning
confidence: 99%